Carbon bridge: making businesses greener by realizing the potential of biochar - impact: elevating our customers success - Siebels, Sara Serra (2023)
This work project discusses the development of the impact business Carbon Bridge. Carbon Bridge has the mission of increasing the sale of biochar by raising awareness for it. While doing so it is aiding businesses to reduce their emissions with biochar. The project, guided by the Plan-Do-Check-Act framework, evolved from an initial vision to a multifaceted product which was further developed using the Lean Business Model Canvas. The final product is a website that includes an educational blog, a Python-built impact assessment tool, and a marketplace for biochar. Upon the reflection of this progress, the work extends with a discussion of customer success. More importantly how Carbon Bridge’s platform and marketplace can positively impact our customers success based on the three pilar approach. It distills the biochar producers needs and expectations based on direct conversations and how we aim to build trust-based relationships to lay the foundation of a strong, long-term bond.